Assessing the Impact of Risk Management Practices on Financial Performance of Banking Sector Companies Listed on IDX 2021-2023 - Patricia Olivia Sijabat; Ery Yanto (Publikasi Indonesia, 2026)
This study aims to assess the impact of risk management practices on the financial performance of banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The banking industry faces various types of risks that can affect financial performance, including credit risk, market risk, liquidity risk, and operational risk. Effective risk management practices are essential for maintaining bank stability and ensuring sustainable profitability. This research employs a quantitative approach using multiple linear regression analysis. The sample consists of 12 banking companies selected through purposive sampling based on specific criteria, including the consistent publication of financial reports during the study period and the completeness of the required data. Data were collected from annual financial reports accessed through the IDX website and the official company websites. The analysis was conducted using SPSS software and included descriptive statistics, classical assumption tests (multicollinearity, normality, heteroskedasticity, and autocorrelation), and hypothesis testing (t-test, F-test, and coefficient of determination). The results indicate that, collectively, credit risk, market risk, liquidity risk, and operational risk have a significant effect on financial performance, with an F-value of 13.160 and a significance level of 0.000. Partially, only liquidity risk shows a significant negative effect on financial performance (t = ?2.308, sig. = 0.028), while credit risk (t = 1.288, sig. = 0.207), market risk (t = 1.409, sig. = 0.169), and operational risk (t = ?1.170, sig. = 0.251) do not have a significant individual effect.